Santiago SEVILLA VALLEJO, "Cómo escribir ficciones según Gonzalo Torrente Ballester. Juego y Literatura, las voces narrativas y las esferas de realidad". Madrid, Editorial Académica Española, 2017, 416 pp. - Zuloaga Jiménez, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
In the book that is going to be reviewed, Santiago Sevilla Vallejo tries to analyze the narrative voice in Gonzalo Torrente Ballester´s novels to see how it could useful for fiction writers.
Keywords: narrator, narrative voice, fiction, novel.